Hurel 2023. Tales, Fables and Narratives of Rwanda - Schmidt, Sigrid (AAeO - Afrikanistik-Aegyptologie-Online, 2024)
Review of a new revised edition of the collection La poésie chez les primitifs ou Contes, fables, récits et proverbes du Rwanda (Lac Kivu) by the Belgian missionary Eugène Hurel, originally published in 1922.